MACROECONOMIA DO BRASIL PÓS-1994 - Bresser-Pereira, Luiz Carlos (Análise Econômica, 2009)
The Brazilian macroeconomic model is characterized by financial opening, a growth strategy based on foreign savings, low (overvalued) exchange rate, current account deficits, high foreign debt, high basic (Selic) interest rate, low but inertial inflation, soft fiscal policy negative public savings, high public debt, depressed expected rates of profit, stagnant salary rate, depressed domestic savings, depressed investments, high unemployment, per capita GDP quasi-stagnant. The Brazilian economy achieved price but not macroeconomic stabilization in 1994 as long as intertemporal equilibrium was not achieved in fiscal and external accounts areas. Growth will only be resumed if monetary authorities acknowledge the interest rate and exchange rate trap in which the Brazilian economy is immersed, and decide to invert the perverse macroeconomic equation of high basic interest rate and low exchange rate. Yet, the international and domestic orthodoxy that runs macroeconomic policy in Brazil keeps using conventional macroeconomics to understand problems which are not conventional, and, so, it is unable to achieve the required macroeconomic stabilization.